The evolving role of truncal fascial plane blocks in non-surgical pain therapy: a narrative review - Gu, Yi; Qin, Yifan; Wu, Jin (Frontiers in Medicine, 2025)
Truncal fascial plane blocks (TFPBs), including erector spinae plane block (ESPB), quadratus lumborum block (QLB), transversus abdominis plane block (TAPB), and serratus anterior plane block (SAPB), are regional anesthesia techniques that achieves analgesia by injecting local anesthetics into a specific fascial planes of the trunk, which is primarily used for postoperative pain management or multimodal analgesia regimens. TFPBs reduce surgical site pain by blocking nerve conduction while decreasing reliance on systemic analgesics, such as opioids. This narrative review evaluates the analgesic efficacy and mechanisms of TFPB in non-surgical pain management, exploring their clinical value and future development prospects.